PENERAPAN MODEL PEMBELAJARAN STAD DAN SAVI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V MANDURIAN KABUPATEN TAPIN KALIMANTAN SELATAN - Rianty Yulandra; Pratiwi Pujiastuti (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2018)
This study aims to describe the implementation and improvement of teacher activity, student activities, and student learning outcomes using Student Teams-Achievement Divisions (STAD) variations of Somatic, Auditory, Visual, Intellectual (SAVI) models on Simple Aircraft material. This type of research is Classroom Action Research (PTK). The subjects of this study were the students of Grade V of SDN Mandurian of Tapin Regency of academic year 2014/2015 semester 2. The result of this research is the application of Student Teams-Achievement Divisions (STAD) variation of Somatic, Auditory, Visual, Intellectual (SAVI) model, , student activity, and student learning result of grade V SDN Mandurian of Tapin Regency on Simple Aircraft material. The learning steps can be explained as follows: (1) Teachers form groups of 4-5 people heterogeneously, (2) Teacher presents lessons, (3) Teacher gives assignments to groups to be undertaken by group members. A member who has understood can explain to the other members until all the members in the group understand, (4) The teacher gives quiz / question to all students, (5) The teacher asks the students to paste the group work, (6) The teacher asks the students for presentation and discussion, (7) Announcement of the winning group.